Facile preparation of PVA hydrogels with adhesive, self-healing, antimicrobial, and on-demand removable capabilities for rapid hemostasis. (22nd August 2022) - He, Yuanmeng; Liu, Kaiyue; Zhang, Chen; Guo, Shen; Chang, Rong; Guan, Fangxia; Yao, Minghao
Abstract : A novel PBO hydrogel based on PVA, borax and oligomeric procyanidin was designed with adhesive, self-healing, antimicrobial, and on-demand removable capabilities for rapid hemostasis. Abstract : Multifunctional and smart hydrogel-based hemostatic materials are of great significance in the field of medical care. In this paper, a facile method for the preparation of self-healing, adhesive and on-demand removable PBO hydrogels was established with a simple mixture of polyvinyl alcohol (PVA), borax and oligomeric procyanidin (OPC). In this hydrogel system, borax and OPC were used as dynamic crosslinkers to connect the PVA macromolecules through reversible borate ester bonds and hydrogen bonds, resulting in hydrogels that possess good self-healing and adhesive abilities. Furthermore, the PBO hydrogel displayed excellent antimicrobial activity against Escherichia coli and Staphylococcus aureus . In addition, thanks to the adhesive property of the hydrogel and the inherent hemostatic activity of OPC, this hydrogel showed rapid hemostasis performance as concluded from the in vivo experiments of mouse liver incision, tail amputation and femoral artery models. Benefitting from the fast degradation in water, this hydrogel could be easily removed on-demand within 10 min. Therefore, this well-designed PBO hydrogel offers an important prospect as a rapid hemostatic dressing.